Electromagnetic Wave Absorbing Properties of Double-Layer Cement Composite and Theory Analysis - Zhang, Yuefang; Hao, Wanjun; Li, Baoyi; Duan, Yuping; Liu, Shunhua (Asian Journal of Chemistry, 2014)
In this paper, we have developed double-layer cement matrix composites by using impedance matching design. Expanded polystyrene beads were used as an electromagnetically transparent material in the composites. The composites’ electromagnetic wave absorption properties (filled with carbon black, manganese dioxide and Ni-Zn ferrite at 2.6-18 GHz) were examined. The results showed that the expanded polystyrene beads significantly improved the impedance matching characteristics between the composites and the free space and the scattering properties of expanded polystyrene beads contributed to further wave attenuation. We further optimized the cement matrix’s absorption properties by altering the ratios of fillers, absorbent types and specimen thicknesses. A maximum absorption of -22.3 dB at 4.8 GHz (bandwidth 11.4 GHz, < -10dB) was achieved under the following conditions: matching layer of 60 vol % expanded polystyrene and 4 vol % ferrite, absorbing layer of 50 vol % expanded polystyrene and 6 vol % carbon black and a specimen thickness of 20 mm.